Performance Measurement and Evaluated on The Lean Accounting (Journal of Accounting and Financial Studies ( JAFS ), 2019)
At the last two decades , The environment has witnessed tremendous changes in many fields with the huge competition , various technological development and customer satisfaction , that are reflected in economic units a doption for lean production system.      Lean accounting that has appeared as a response for change occurred of economic units adoption for changes occurred of economic units adoption for lean production instead of wide production system , has devised new performance measures suitable for economic units adoption for lean ideas: and helping in providing suitable information about evaluating economic unit performance , these measures are divided into three levels , cell level,value flow level , and economic unit level.